Efficacy of non-surgical interventions for promoting improved functional outcomes following acute compartment syndrome: A systematic review. - Naveena B Janakiram; Jessica M Motherwell; Stephen M Goldman; Christopher L Dearth (PLoS ONE, 2022)
Background Acute compartment syndrome (ACS) is a devastating complication which develops following a traumatic extremity injury that results in increased pressure within osteofascial compartments, thereby leading to ischemia, muscle and nerve necrosis, and creates a life-threatening condition if left untreated. Fasciotomy is the only available standard surgical intervention for ACS. Following fasciotomy the affected extremity is plagued by prolonged impairments in function. As such, an unmet clinical need exists for adjunct, non-surgical therapies which can facilitate accelerated functional recovery following ACS. Thus, the purpose of this systematic review was to examine the state of the literature for non-surgical interventions that aim to improve muscle contractile functional recovery of the affected limb following ACS. Methods English language manuscripts which evaluated non-surgical interventions for ACS, namely those which evaluated the function of the affected extremity, were identified as per PRISMA protocols via searches within three databases from inception to February 2022. Qualitative narrative data synthesis was performed including: study characteristics, type of interventions, quality, and outcomes. Risk of bias (RoB) was assessed using the Systematic Review Centre for Laboratory Animal Experimentation's (SYRCLE) RoB tool and reported level of evidence for each article. Results Upon review of all initially identified reports, 29 studies were found to be eligible and included. 23 distinct non-surgical interventions were found to facilitate improved muscle contractile function following ACS. Out of 29 studies, 15 studies which evaluated chemical and biological interventions, showed large effect sizes for muscle function improvement. Conclusions This systematic review demonstrated that the majority of identified non-surgical interventions facilitated an improvement in muscle contractile function following pathological conditions of ACS.